2019 Tenth International Green and Sustainable Computing Conference (IGSC) 2019
DOI: 10.1109/igsc48788.2019.8957182
|View full text |Cite
|
Sign up to set email alerts
|

SCART: Predicting STT-RAM Cache Retention Times Using Machine Learning

Abstract: Prior studies have shown that the retention time of the non-volatile spin-transfer torque RAM (STT-RAM) can be relaxed in order to reduce STT-RAM's write energy and latency. However, since different applications may require different retention times, STT-RAM retention times must be critically explored to satisfy various applications' needs. This process can be challenging due to exploration overhead, and exacerbated by the fact that STT-RAM caches are emerging and are not readily available for design time expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The traditional CPU does not have any PiC/PiM optimization but features a relaxed retention STT-RAM cache of 75µs at L1 and 10ms at L2. Many prior works have indicated several energy and area benefits of replacing SRAM caches with STT-RAMs in different memory levels of traditional CPU-based computing [7], [14], [32], [33]. Thus, using STT-RAM caches with the base CPU allows us to robustly evaluate the added benefits of PiC/PiM architecture using STT-RAMs.…”
Section: Results and Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…The traditional CPU does not have any PiC/PiM optimization but features a relaxed retention STT-RAM cache of 75µs at L1 and 10ms at L2. Many prior works have indicated several energy and area benefits of replacing SRAM caches with STT-RAMs in different memory levels of traditional CPU-based computing [7], [14], [32], [33]. Thus, using STT-RAM caches with the base CPU allows us to robustly evaluate the added benefits of PiC/PiM architecture using STT-RAMs.…”
Section: Results and Analysismentioning
confidence: 99%
“…They utilized a sampling-based algorithm to determine the most suitable retention times for different applications dynamically. Similarly, Gajaria et al [14] found that specializing retention times of STT-RAM caches to the application needs improved performance and energy savings by 20.34% and 29.12%, respectively. In our work, we explore how relaxed retention STT-RAM can improve the efficiency of PiC operations.…”
Section: B Relaxed-retention Stt-ram Cachesmentioning
confidence: 93%
See 2 more Smart Citations
“…These NVM technologies offer diverse solutions for nonvolatile data storage with various advantages and characteristics. For instance, STT-MRAM has smaller cell area compared to SRAM, maintaining low programming voltage, fast write/read speed, and long endurance, making it an attractive replacement for embedded memories in the last level-cache and main memories [15], [16], [17]. PCRAM and ReRAM offer low programming voltage and fast write/read speed, making them attractive as a replacement for existing technologies in resource-constrained memory systems.…”
Section: A Overview Of Emerging Memory Technologiesmentioning
confidence: 99%